GAMBARAN KADAR CRP PADA MENCIT ALERGI SETELAH TREATMENT INFUSA DAUN KETEPENG - Firmansyah, Adi; I Gede Andika Sukarya; Suryanata Kesuma (LPPM STIKes Mitra Adiguna, 2024)
Allergy is a hypersensitivity reaction that arises due to exposure to allergens. Allergens will bind to IgE attached to mast cells and cause these cells to release various chemicals in the blood. One of them is, histamine which causes most allergic reactions. Allergic reactions can cause inflammation or inflammation. Inflammatory stimulation will later stimulate the release of C-Reactive Protein (CRP). CRP is an inflammatory maker that is produced and synthesized in the liver. Ketepeng leaf infusion has the potential to stimulate an immune response because it contains chemical compounds, namely alkaloids, saponins, flavonoids, tannins, and anthracino. Flavonoids contained in this plant function to provide anti-inflammatory, antiallergic, antioxidant and antifungal effects. The purpose of this study was to determine the effectiveness of ketepeng leaves (Cassia alata L) by examining CRP (C-Reactive Protein) levels in Ovalbumin-allergic mice (Mus musculus). This type of research is Univariate, which is a method for making an overview of the state of the object being examined through data or sampling samples. The results of this study found that in group 2 after being given ovalbumin, CRP levels increased by 181.33 mg/L and in group 3, after being given ketepeng leaf infusion, CRP levels decreased by 48 mg/L. The conclusion of this study is that ketepeng leaf infusion can reduce CRP levels in mice with ovalbumin allergy and there is an effect of increasing CRP levels in mice given ovalbumin of 181.33 mg/L and a decrease in CRP levels after the treatment of ketepeng leaf infusion of 48 mg/L .